Incidence and Risk Factors for Isolated Esophageal Cancer Recurrence to the Brain - Nobel, Tamar (Ann Thorac Surg, 2019)
BACKGROUND: Recurrence of esophageal cancer in the brain is rare but associated with poor prognosis. Identification of risk factors for isolated brain metastasis after surgical treatment (iBMEC) may guide surveillance recommendations to enable early identification and intervention prior to widespread metastasis. METHODS: Patients with iBMEC (n=38) were identified from a prospective database of patients with esophageal cancer that underwent esophagectomy. Risk factors for iBMEC were identified using competing risk regression analysis. RESULTS: In a cohort of 1760 patients, 39% recurred and 2% developed iBMEC by the end of the study. Patients with iBMEC had similar survival to patients with distant recurrence (median OS: 0.95 years, 95%CI 0.6–1.5). Over half of patients with iBMEC were diagnosed within 1 year postoperatively. All 38 patients with iBMEC had received neoadjuvant therapy prior to surgery. Pathologic Complete Response (PCR) to neoadjuvant therapy was associated with improved survival after brain recurrence (median OS:1.56 years versus 0.66, p=0.019). CONCLUSIONS: In patients with PCR, iBMEC may represent true isolated recurrence while in those with residual nodal disease, iBMEC may actually be the first observed site of widespread metastasis. Patients that received neoadjuvant therapy, especially with PCR, may benefit from brain imaging, both preoperatively and with routine surveillance.